Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai di Dinas Pendidikan Provinsi Jambi - AZ, Siti Marina; Ratna, Ratna; Maisarah, Siti (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of leadership style on teacher work motivation on staff performance at the Jambi Provincial Education Office. This research includes quantitative descriptive research. The population of this study was 60 people. The research results show that leadership style and motivation have a significant influence on performance, with an Adjusted R Square value of 0.406 on performance.